Computer and electronic devices waste: analytical study - Hameed, Shihab A.; Khalifa, Othman Omran (2011)

(untitled)
In last few decades; Computers and electronic devices production and consumption has grown rapidly; since such devices has greatly improved our quality of life; but on the other hand it also created environmental problem ; e-waste. Studies show that worldwide; millions of tons of garbage generated yearly as e-waste. E-waste is more toxic and harmful than normal household garbage. E-waste is growing rapidly compared to other household waste. Computers and electronic waste contain toxic heavy metals, including arsenic, antimony, lead, mercury, nickel, and zinc. It is estimated that about 40% of all heavy metals in household garbage comes from electronic equipment. The UN estimates about 50 million tons of e-waste may be generated in world yearly, but small percentage of it are recycled. Incomplete technology and competitions between electronic production companies leads to agile products with small change in term of functionality or design; Mobile phones with new multi-functions, ever lighter notebooks and flatter TV screens are quickly replacing outdated products. This was associated with heavy announcements in different media, which affected not small ratio of customers. As the consumption of electronics has boomed, so have the waste amounts generated by discarded products. New EC legislation requires that the cost of properly disposing of electronic products must be picked up by the producers of the waste (manufacturers, retailers, branders, and importers). Consequently, creative minds at several electronics companies have been set in motion aimed at producing more eco-friendly products that are easier to recycle and handle when they reach their end-of-life. This positive EU trend will have global effects, since the electronics market and production, process is global. However, several developing countries in Asia, Africa and Latin America suffer from lack of proper systems for recycling and disposal treatment experience; this leads to increase e-waste problems because of increasing consumption of electronics in these countries at present and e-waste is exported from the industrial world to developing nations. UNEP (2009) and other studies show that in informal recycling in countries such as China, India, Ghana, Nigeria, and Mexico; workers are exposed to hazardous chemicals and material when products are broken apart to extract valuable content. On the other hand, the water, air, and soil are also polluted. This paper study and analyze status of computer and electronic devices Waste based on statistics and studies done in several counties. It proposes an effective fundamental guidance to eliminate and control e-waste as well as protecting worker and environment in developing world.